Transformation of Social Capital in Urban Communities in the Digital Era: A Study of Changing Patterns of Solidarity and Social Participation - Ika Rahma (Archipel: Journal of Indonesian Interdisciplinary Studies, 2025)
This study examines the transformation of social capital in urban communities in the digital era through a literature review of recent scientific publications. The main focus is mapping changes in the structure of social relations, patterns of social solidarity, and community participation due to the digitalization of social interactions. The review process included identification, selection, and thematic analysis of literature related to social capital, community digitalization, solidarity, and social participation from various national and international journals. The findings indicate that digitalization expands social networks but tends to weaken the depth of interpersonal relationships, and shifts the mechanisms of solidarity formation to issue-based and more symbolic digital participation. The results also highlight the challenges of digital literacy and the gap in technology access that affect the distribution of social capital in urban communities. This article presents an argumentative synthesis of the changing dimensions of social capital and its implications for urban social cohesion. This research is expected to serve as a conceptual foundation for further empirical research and for the formulation of inclusive digital interaction-based social policies. The findings demonstrate the urgency of integrating online and offline relationships to strengthen the social capital of urban communities sustainably.